2016
DOI: 10.5935/1678-9741.20160025
|View full text |Cite
|
Sign up to set email alerts
|

Associated Clinical and Laboratory Markers of Donor on Allograft Function After Heart Transplant

Abstract: IntroductionPrimary graft dysfunction is a major cause of mortality after heart transplantation.ObjectiveTo evaluate correlations between donor-related clinical/biochemical markers and the occurrence of primary graft dysfunction/clinical outcomes of recipients within 30 days of transplant.MethodsThe prospective study involved 43 donor/recipient pairs. Data collected from donors included demographic and echocardiographic information, noradrenaline administration rates and concentrations of soluble tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…A Brazilian group showed recipients receiving grafts from donors expressing lower concentrations of plasma soluble tumour necrosis factor receptors 2 (sTNFR2) and IL-6, required more inotropic support post-transplantation [145].…”
Section: Primary Graft Dysfunctionmentioning
confidence: 99%
“…A Brazilian group showed recipients receiving grafts from donors expressing lower concentrations of plasma soluble tumour necrosis factor receptors 2 (sTNFR2) and IL-6, required more inotropic support post-transplantation [145].…”
Section: Primary Graft Dysfunctionmentioning
confidence: 99%
“…After surgery, graft inflammation may respond to several mechanisms, from alloantigen‐directed immune reactions of the recipient resulting in graft rejection to ischaemia/reperfusion injury of the graft 7. Inflammation of the donor before explantation is also associated with worse outcome of the recipient 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…7 Inflammation of the donor before explantation is also associated with worse outcome of the recipient. 8,9 Neutrophil-to-lymphocyte ratio (NLR) is a marker of inflammation. First described in 1967 as an indicator of ozone exposure, 10 NLR has shown prognostic value in different cardiovascular conditions including stable coronary artery disease, acute coronary syndromes, HF, and coronary artery bypass grafting (CABG).…”
Section: Introductionmentioning
confidence: 99%
“…Inotropic support is vital for management of the hemodynamic compromise during donor BD, however, in a potentially desensitized organ, additional exogenous catecholamine exposure may only add insult to injury. Indeed, high inotrope dependence and significant myocardial dysfunction can prohibit organ donation (based on medical grounds) [340,341]. Due to the shortage of acceptable donor hearts, several studies have demonstrated that using these “extended criteria” donors on high inotrope support is an acceptable strategy for expanding the donor pool [342,343,344].…”
Section: Cardioprotection With Inotropic Supportmentioning
confidence: 99%